The Influence of Work Motivation, Work Discipline and Work Environment on Teacher Performance at SMA Negeri 2 Tebing Tinggi - Suwadi (Journal of Economics, Management, Development, and Education, 2026)
This study aims to analyze and determine the influence of Work Motivation, Work Discipline, and Work Environment on Teacher Performance at SMA Negeri 2 Tebing Tinggi. This study is a replication study using a quantitative approach. Research data were obtained through distributing questionnaires to 67 respondents who are teachers at SMA Negeri 2 Tebing Tinggi. Data analysis was carried out using Statistical Product and Service Solutions (SPSS) software version 25.00. The results of the study indicate that the Work Motivation variable does not have a significant effect on Teacher Performance. This is evidenced by the calculated t value of 0.269 which is smaller than the t table of 1.66 and the significance value of 0.789 which is greater than 0.05. The variables of Work Discipline and Work Environment have a positive and significant effect on Teacher Performance. The calculated t value of Work Discipline is 3.797 and the Work Environment is 13.970, both of which are greater than the t table of 1.66 with a significance value of 0.000 which is smaller than 0.05. Simultaneously, Work Motivation, Work Discipline, and Work Environment have a significant effect on Teacher Performance, which is indicated by the calculated F value of 188.469 which is greater than the F table of 2.75 with a significance level of 0.000. This study shows that increasing work discipline and a conducive work environment can improve teacher performance optimally.